2006
DOI: 10.1080/17450390600884500
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a herbal product againstHistomonas meleagridisafter experimental infection of turkey poults

Abstract: Histomoniasis (infectious enterohepatitis, blackhead) is caused by the protozoan parasite Histomonas meleagridis (H. meleagridis). After the ban of all prophylactic and therapeutic drugs in the European Union, histomoniasis is increasingly responsible for considerable economic problems to the poultry industry. The aim of this study was to investigate the effect of a herbal product with extracts from cinnamon, garlic, lemon, and rosemary on H. meleagridis in turkey poults in vivo. For this purpose, 60 two-week-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 19 publications
1
24
1
1
Order By: Relevance
“…The latter finding is in agreement with the results of a field study in turkeys (Chossat, 2002), but in contrast with a recent in vivo experiment (Hafez & Hauck, 2006). In the latter study turkeys provided with Protophyt™ SP in the feed six days before inoculation and Protophyt™ B in the drinking water three days before inoculation showed 20% mortality instead of 50% mortality in the positive control group after experimental inoculation with 147500 histomonads per bird.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…The latter finding is in agreement with the results of a field study in turkeys (Chossat, 2002), but in contrast with a recent in vivo experiment (Hafez & Hauck, 2006). In the latter study turkeys provided with Protophyt™ SP in the feed six days before inoculation and Protophyt™ B in the drinking water three days before inoculation showed 20% mortality instead of 50% mortality in the positive control group after experimental inoculation with 147500 histomonads per bird.…”
Section: Discussionsupporting
confidence: 43%
“…Therefore, there is an urgent need for alternative antihistomonal products (Hu & McDougald, 2004). In the field, herbal products are used to prevent outbreaks of histomoniasis (Hafez & Hauck, 2006). However there are only a few scientific in vivo studies backing up the efficacy of such products against H. meleagridis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro and in vivo experimental studies on chemotherapeutics have shown variable outcomes in finding a new and efficient therapy against H. meleagridis infections (Hu & McDougald, 2002;Hafez & Hauck, 2006;Bleyen et al, 2009;Hafez et al, 2010;Hauck et al, 2010b). Within recent years a trend towards non-chemotherapeutic alternative means has been set in the combat of histomonosis.…”
Section: Introductionmentioning
confidence: 99%
“…From among the former group, only Histostat (nitarsone) has received FDA approval solely for prevention, and from among the latter, the most effective one, dimetridazole, which has been banned in animals for its carcinogenic, mutagenic, and genotoxic effects 6,7 . As a result, a treatment gap exists for histomoniasis which calls for attention 8 . The use of medicinal herbs which are widely available and inexpensive and have few side-effects may be the answer.…”
Section: Introduction: the Protozoan Parasitementioning
confidence: 99%